2022
DOI: 10.3389/fcvm.2022.845673
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Exosomal S1PR5 and CARNS1 as Potential Non-invasive Screening Biomarkers of Coronary Heart Disease

Abstract: BackgroundEarly diagnosis and treatment significantly improve the prognosis of coronary heart disease (CHD), but no convenient screening tools are available. This study aims to find potential non-invasive screening biomarkers of coronary heart disease.MethodWe performed microarray analysis to investigate the mRNA expression levels in Small extracellular vesicles (sEVs) and screen significantly differentially expressed mRNAs in CHD patients vs. non-CHD patients. We then performed quantitative real-time polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…For a more in-depth understanding of these DEGs, we analyzed the selected genes for GO and REACTOME pathway enrichment analyses and found that GO terms and signaling pathways were significant. [106], FCN1 [107], CARNS1 [108], AMH (anti-Mullerian hormone) [109], E2F1 [110], PF4 [111], RPL3L [112], TRIM72 [113], HOXB4 [114], TP73 [115], KCNH2 [116], (advanced glycosylation end-product specific receptor) [117], SMPD3 [118], TYMP (thymidine phosphorylase) [119], RIPPLY3 [120], GREM1 [121], CYP11B2 [122], MYLK2 [123], WNT3A [124], MSX1 [125], COMP (cartilage oligomeric matrix protein) [126], FLI1 [127], ACTA1 [128], TCAP (titincap) [129], TUBB1 [130], TNNI3 [131], HSPB7 [132], DES (desmin) [133], RAP1B [134], TNNT1 [135], BHMT (betaine--homocysteine S-methyltransferase) [136], ANGPTL3 [137], CYP3A5 [138], KMO (kynurenine 3-monooxygenase) [139], HMGCS2 [140], AGXT2 [141], FABP1 [142], SLC22A12 [143], CUBN (cubilin) [144], MIOX (myo-inositol oxygenase) [145], FBP1 [146], ARG2 [147], FGF1 [148], CRY1 [149], PPARGC1A [150], UGT1A6 [151], ECHDC3 [152], CYP2C8 [153], ACOX2…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a more in-depth understanding of these DEGs, we analyzed the selected genes for GO and REACTOME pathway enrichment analyses and found that GO terms and signaling pathways were significant. [106], FCN1 [107], CARNS1 [108], AMH (anti-Mullerian hormone) [109], E2F1 [110], PF4 [111], RPL3L [112], TRIM72 [113], HOXB4 [114], TP73 [115], KCNH2 [116], (advanced glycosylation end-product specific receptor) [117], SMPD3 [118], TYMP (thymidine phosphorylase) [119], RIPPLY3 [120], GREM1 [121], CYP11B2 [122], MYLK2 [123], WNT3A [124], MSX1 [125], COMP (cartilage oligomeric matrix protein) [126], FLI1 [127], ACTA1 [128], TCAP (titincap) [129], TUBB1 [130], TNNI3 [131], HSPB7 [132], DES (desmin) [133], RAP1B [134], TNNT1 [135], BHMT (betaine--homocysteine S-methyltransferase) [136], ANGPTL3 [137], CYP3A5 [138], KMO (kynurenine 3-monooxygenase) [139], HMGCS2 [140], AGXT2 [141], FABP1 [142], SLC22A12 [143], CUBN (cubilin) [144], MIOX (myo-inositol oxygenase) [145], FBP1 [146], ARG2 [147], FGF1 [148], CRY1 [149], PPARGC1A [150], UGT1A6 [151], ECHDC3 [152], CYP2C8 [153], ACOX2…”
Section: Discussionmentioning
confidence: 99%
“…Signaling pathways include neuronal system [90], GPCR ligand binding [91], metabolism [92] and metabolism of lipids [93] were responsible for progression of AKI. MYH7 [94], BMI1 [95], IGF2 [96], ADORA2A [97], KLK10 [98], MEIS2 [99], IRF7 [100], PRKCB (protein kinase C beta) [101], CCL5 [102], ADAM33 [103], EEF1A2 [104], ACTN3 [105], TRIM65 [106], FCN1 [107], CARNS1 [108], AMH (anti-Mullerian hormone) [109], E2F1 [110], PF4 [111], RPL3L [112], TRIM72 [113], HOXB4 [114], TP73 [115], KCNH2 [116], (advanced glycosylation end-product specific receptor) [117], SMPD3 [118], TYMP (thymidine phosphorylase) [119], RIPPLY3 [120], GREM1 [121], CYP11B2 [122], MYLK2 [123], WNT3A [124], MSX1 [125], COMP (cartilage oligomeric matrix protein) [126], FLI1 [127], ACTA1 [128], TCAP (titin-cap) [129], TUBB1 [130], TNNI3 [131], HSPB7 [132], DES (desmin) [133], RAP1B [134], TNNT1 [135], BHMT (betaine--homocysteine S-methyltransferase) [136], ANGPTL3 [137], CYP3A5 [138], KMO (kynurenine 3-monooxygenase) [139], HMGCS2 [140], AGXT2 [141], FABP1 [142], SLC22A12 [143], CUBN (cubilin) [144], MIOX (myo-inositol oxygenase) [145], FBP1 [146], ARG2 [147], FGF1 [148], CRY1 [149], PPARGC1A [150], UGT1A6 [151], ECHDC3 [152], CYP2C8 [153], ACOX2 [154], SLC2A9 [155], MSRA (methionine sulfoxidereductase A) [156], GC (GC vitamin D binding protein) [157], VNN1 [158], NOX4 [159], GOT2 [160], EPHX2 […”
Section: Discussionmentioning
confidence: 99%
“…3 CAG and CCTA are effective methods for diagnosing CHD, but there are limitations to their application due to patient conditions, technical requirements, and cost issues. 8,9,20 Subsequently, the AHA/ACC and ESC proposed the DCS and UDFM models to calculate PTPs for guidance in CAG selection. Still, the above models overestimated the prevalence of CHD.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CCL18 [109], SLAMF7 [110], GPR174 [111], CCR4 [112], POU4F2 [113]. CCR2 [114], IL2RB [115], CCL4 [116], CCL24 [117], FASLG (Fas ligand) [118], CD24 [119], TDGF1 [120], CD28 [121], IL7R [122], CYP11B1 [123], CCL5 [124], CCL3 [125], LTF (lactotransferrin) [126], GPNMB (glycoprotein nmb) [127], CD209 [128], IL2RG [129], CHIT1 [130], TAB2 [131], CD163 [132], ALOX15B [133], NMRK2 [134], HGF (hepatocyte growth factor) [135], TRPM8 [136], DIO3 [137], SIGLEC1 [138], TTR (transthyretin) [139], IL24 [140], F13A1 [141], IL9 [142], VEGFA (vascular endothelial growth factor A) [143], RASAL1 [144], ADM (adrenomedullin) [145], ANGPTL4 [146], CHI3L1 [147], LDB3 [148], CNP (2’,3’-cyclic nucleotide 3’ phosphodiesterase) [149], HES6 [150], CMTM5 [151], PLXNB3 [152], KLK8 [153], CDKN1C [154], INSIG1 [155], GREM1 [156], ATF3 [157], HK2 [158], MCAM (melanoma cell adhesion molecule) [159], SEMA4D [160], GLUL (glutamate-ammonia ligase) [161], S1PR5 [162], FN3K [163], MEIS1 [164], ADAMTS4 [165], BIN1 [166], BMP2 [167], LMNA (lamin A/C) [168], ERBB3 [169], DLL1 [170], THBS2 [171], GADD45B [172], MYH6 [173]. PNPLA3 [174], ACTN2 [175], MMP15 [176], SVEP1 [177], CPB2 [178], DYSF (dysferlin) [179], ADAMTSL2 [180], NINJ2 [181], LRP2 [106], PHLDA3 […”
Section: Discussionmentioning
confidence: 99%